Accelerating reinforcement learning by reusing abstract policies - Bergamo, Yannick Plaino; Matos, Tiago; Silva, Valdinei Freire da; Costa, Anna Helena Reali (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2011)
Reinforcement learning (RL) provides a general approach for developing intelligent agents that are able to optimize their behaviors in stochastic environments. Unfortunately, most work in RL is based on propositional representations, making it difficult to apply it to more complex real-world tasks in which states and actions are more naturally represented in relational form. Moreover, most work in RL does not take into account existing solutions to similar problems when learning a policy to solve a new problem, and consequently solves the new problem from scratch, what can be very time consuming. In this article we explore the powerful possibilities of using relational descriptions so that we can learn abstract policies, and in reusing these policies to improve initial performance of an RL learner in a similar new problem. Experiments carried out attest the effectiveness of our proposal.